Los sistemas contables informáticos y su incidencia en el desarrollo de pasantías en las empresas públicas y privadas de los estudiantes del tercer año de bachillerato técnico de la especialidad de contabilidad del Instituto Tecnológico Superior Dr. José Ochoa León en el período lectivo 2013 -2014. - Amaya Delgado, Diana Belen (2015)
This research addresses the theme of the use of accounting systems in the classroom and their impact on the process of conducting internship students of the third year of accounting specialty technical school Superior Technological Institute "Dr. Jose Ochoa Leon" of Pasaje city, El Oro province. Ecuador. The investigation was based on methodological processes characteristic of proactive diagnostic modality, making a tour of the operational procedure which led to verify the problems that arose with the objectives, likewise the proposed hypotheses were tested once the data collected, analyzed and interpreted, activity that resulted from the implementation of the survey and interview students to teachers. After this activity I proceeded to draw the conclusions and recommendations that they led to propose conferences of induction to teachers on the use of the financial system, particularly the so-called Monica 9.0, in order to use this tool in their classes and Students can apply the accounting processes relying on a specific computer tool, this will certainly help in developing their internships in companies since now a good number of them have implemented. This type of system but it should be clarified that these programs can vary according to the needs of the organization. Similarly it contributes to motivation in class, improved teaching and learning processes and increased institutional prestige for the quality of students which gives the society.